Outcomes of post-traumatic tibial osteomyelitis treated with an Orthofix LRS versus an Ilizarov external fixator. Issue 7 (July 2017) - Yilihamu, Yilizati; Keremu, Ajimu; Abulaiti, Alimujiang; Maimaiti, Xiayimaierdan; Ren, Peng; Yusufu, Aihemaitijiang
Abstract: Objective: To compare the therapeutic effects of the Orthofix limb reconstruction system (LRS) versus the Ilizarov external fixator on osteomyelitis of a tibial bone defect. Materials and methods: Among 153 patients hospitalized for bone lengthening therapy from January 1, 1996 to January 1, 2015, 129 patients were selected for a retrospective analysis. Forty-three of the candidate patients were treated using the Orthofix LRS and the other 86 were treated using an Ilizarov external fixator. The average follow-up was 96 months. We evaluated the patients at follow-up visits, and compared the length of time the patients wore the fixation devices. We also examined the scores of Activities of Daily Living (ADL) tests and a Self-rated Anxiety Scale (SAS), the range of motion, and the incidence of pin track infections. Results: The results indicated that both approaches were effective for treating the bone defect. Compared with the patients who wore an Ilizarov fixator for the treatment of post-traumatic osteomyelitis, those who wore an Orthofix LRS tended to be more satisfied with their quality of life and the outcome after the operation. Conclusion: Although both approaches were effective for treating the bone defect, the overall patient outcomes were superior for the Orthofix LRS, suggesting that it should be considered as the first option in the treatment of traumatic osteomyelitis of the tibial diaphysis.